ANALYSIS OF JUNIOR HIGH SCHOOL STUDENTS ABILITY IN WORKING ON HOTS PROBLEM POINTS ON VIBRATION AND WAVE MATERIAL - Zelda Akhirmaini; Milla Rulisa; Raudhatul Jannah; Fitri Anita; Ahmad Walid (Science Education, Institut Agama Islam Negeri Ponorogo, 2021)
High-level thinking skills are not only established in the cognitive aspect but are able to improve the skills and effective aspects of students. One of the things that is applied to improve the ability to think at a high level is to submit tests for HOTS ( Higher Order Thinking Skills) problem, Given to students to know how much students are able to do and solve problems not only completing but students are required to understand the problems given. This research used quantitative deriftive research design. The data was analyzed using descriptive percentages. Calculate the individual grade of each student of grade VIII A Junior High School 05 Bengkulu City. The results showed that the ability of students of class VIII A Junior High School 05 Kota Bengkulu in working on HOTS problem items on vibration and wave material was in a very low category with a total average of 24.90 of the HOTS issues given. This means that students of class VIII A Junior High School 05 Bengkulu City have not been able to work on HOTS problems on vibration and wave material.